Why do cracks occur in the weld joint of Ti-22Al-25Nb alloy during post-weld heat treatment? - Shao, Ling; Zhang, Xinyu; Chen, Yingwei; Zhu, Liu; Wu, Sujun; Liu, Qijie; Li, Weiwei; Xue, Na; Tu, Zhibiao; Wang, Tianle; Zhang, Jitang; Dai, Sheng; et al. (Frontiers in Materials, 2023)
An ultrasonic pulse frequency tungsten inert gas welding technology was adopted to join Ti-22Al-25Nb alloy. There were some cracks in the weld joint of Ti-22Al-25Nb alloy after post weld heat treatment. The hardness and Young’s modulus of α2, O and β/B2 phases in Ti-22Al-25Nb alloy were examined with in situ nanoindentation technique. The phase transition stress of three different phases in the weld joint of Ti-22Al-25Nb alloy was analyzed to explain why did the cracks take place in the weld joint of Ti-22Al-25Nb alloy during post weld heat treatment process. The results show that the mean hardness of α2 phase is the highest, O phase second and β/B2 phase last, and the mean Young’s modulus has the same trend with the mean hardness in Ti-22Al-25Nb alloy. The phase transition stress results in cracks in the weld joint of Ti-22Al-25Nb alloy during post weld heat treatment process. By improving post weld heat treatment, the ultimate strength of the weld joints of Ti-22Al-25Nb alloy reaches 750 MPa, which is 72.5% of that of the base material.